Faktor-Faktor yang Mempengaruhi Siklus Menstruasi pada Remaja Putri (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the factors that influence the menstrual cycle in adolescent girls at SMA Negeri 2 Ngaglik, explicitly analyzing the influence of body weight, physical activity, and anxiety in teenage girls at SMA Negeri 2 Ngaglik. The method used is quantitative research with descriptive methods and a cross-sectional design. The research results show a significant relationship between body weight and menstrual cycle irregularities with a p-value of 0.001, so the p-value is